LA Academic production in Arts Faculty: A musician´s view. (2014)
This article focuses upon the educational scope of arts in population general education as well as the expected commitment to contributing the cultural process of development by the arts institution and artists involved in educational affairs at Colombian universities. In this way, those artists are challenge to present their creative output and their reflexive writings on the latest altogether as a required accomplishment for achieving the above mentioned contribution as it is regarded as a relevant issue of university mission.